Modelling molecular weight changes induced in polydimethylsiloxane by gamma and electron beam irradiation - Satti, Angel Jose (2008)
A commercial linear polydimethylsiloxane (PDMS) was subject to gamma irradiation under vacuum and in air, as well as to accelerated electron beam radiolysis (EB). All irradiation treatments were done at room temperature. The molecular weight changes induced by the radiation processes have been investigated using size exclusion chromatography (SEC) with refraction index (RI) and multi angle laser light scattering (MALLS) detectors to obtain the number and weight average molecular weights of the irradiated samples. The analysis of the data indicates that crosslinking reactions predominated over scission reactions in all cases. Gamma irradiation under vacuum was the most efficient process within the analyzed dose range, reaching the gel point earlier. Irradiation in the presence of oxygen induces oxidative effects, both in gamma and EB irradiations. A previously developed mathematical model of the irradiation process that accounts for simultaneous scission and crosslinking and allows for both H and Y crosslinks fitted well the measured molecular weight data.